2022
DOI: 10.3390/ijerph19084483
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Access to Information in Times of COVID-19: The Role of Social Work

Abstract: The confinements and limited social interactions that have derived from COVID-19 have aggravated the situation of people with previous pathologies. As a result, access to health and its rehabilitation or support resources has been limited and redirected toward online care. People with mental health problems have considerably suffered during the pandemic because, for many of them, accessing different information resources through telematic means proved to be a great difficulty in their everyday lives. This expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, we have identified in the literature review that there is a gap in analysing particularly how health information from some social workers and related professionals has been used to alleviate the pandemic and lockdown consequences. As identified in the introduction, there are descriptive works and contributions in the field but with a scarcity of focus on social work and related professionals in spite of some efforts [ 11 , 19 ], which has been crucial to attending to vulnerable groups. The health professionals have been at the frontline of COVID-19, but the vision of who works on the frontline [ 22 ] needs to be expanded to other professionals that have been in a similar position, being at risk of or becoming infected because of their work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have identified in the literature review that there is a gap in analysing particularly how health information from some social workers and related professionals has been used to alleviate the pandemic and lockdown consequences. As identified in the introduction, there are descriptive works and contributions in the field but with a scarcity of focus on social work and related professionals in spite of some efforts [ 11 , 19 ], which has been crucial to attending to vulnerable groups. The health professionals have been at the frontline of COVID-19, but the vision of who works on the frontline [ 22 ] needs to be expanded to other professionals that have been in a similar position, being at risk of or becoming infected because of their work.…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, the role of social work and related areas becomes crucial. There is evidence of programmes related to social work implemented in the mental health field [ 19 ] in the pandemic context, and this work aims to advance this knowledge to show the relevance of social work in such a challenging context.…”
Section: Introductionmentioning
confidence: 99%
“…The environment and our perception of it now play a key role in human behavior and, also, in how people act in their daily lives [ 15 ]. In the same line, it has been shown that the way in which a company deals with equality issues determines not only a good working environment and the well-being of its workers, but also its benefits in the market [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has unleashed a global health concern with devastating consequences for the population, especially for the most vulnerable groups [ 29 ]. Beyond the global health problem, 6.28 M people died up until 27 May 2022 [ 30 ], the reality of gender-based violence has caused a problem and aggravated this reality in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Another study with 27 social workers and 22 service users explored their views on ICT-related service delivery [ 10 ]. The third qualitative study with two social workers and nine service users explored the importance of digital communicative competencies in handling and accessing information [ 11 ]. The fourth was our sister study on the internet-based training, learning and sharing platform (i-TLS) use of 313 social workers with quantitative and qualitative evaluation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%